Propulsive forces on water polo players` feet from eggbeater kicking estimated by pressure distribution analysis - Kawai, E.; Tsunokawa, T.; Sakaue, H.; Takagi, H. (Sports Biomechanics, 2023)
The purpose of this study was to characterise the unsteady propulsive force during eggbeater kicking by a fluid force estimation method based on pressure distribution analysis. The eggbeater kick was performed by six male water polo players. The participants` eggbeater kicking motions were recorded by three cameras, and the kinematic foot variables were analysed. The pressure distributions around the foot were measured by four pairs of pressure sensors attached to the dorsal and plantar surfaces of the participants` right foot. The resultant fluid force acting on the foot was estimated from the measured pressure and area of the foot. The calculated propulsive force increased with the pressure difference between the plantar and dorsal sides of the foot, which was mainly related to the decrease in pressure on the dorsal side, and peaked when the foot passed its maximum velocity and began to decelerate. These results cannot be elucidated only by conventional biomechanical theories of swimming propulsion (Newton`s laws of motion and the quasi-steady approach) but instead indicate a high possibility that the exerted propulsive force is induced by the effects of unsteady water flow.